Do pre-school episodic syndromes predict migraine in primary school children? A retrospective cohort study on health care data. (April 2019) - Albers, Lucia; von Kries, Rüdiger; Straube, Andreas; Heinen, Florian; Obermeier, Viola; Landgraf, Mirjam N
Objective: To assess the relative risk, predictive value and population attributable risk fraction of pre-school episodic syndromes for later migraine in primary school age children. Methods: This retrospective cohort study used health insurance data on 55, 035 children born in 2006 with no diagnosis of migraine up to the age of 5 years. The relative risk, probability and population attributable risk fraction of migraine prompting a physician visit at the age of 6–10 years in children with episodic syndromes included in the International Classification of Headache Disorders (benign paroxysmal torticollis, benign paroxysmal vertigo, cyclic vomiting syndrome, recurrent abdominal symptoms and abdominal migraine) and those not included in the International Classification of Headache Disorders (pavor nocturnus, somnabulism and bruxism) diagnosed up to the age of 5 years were determined. Results: The period prevalence of individual episodic syndromes ranged between 0.01% and 1.40%. For episodic syndromes included in the International Classification of Headache Disorders (recurrent abdominal symptoms and abdominal migraine) and for the episodic syndromes not included in the International Classification of Headache Disorders (somnambulism), the risk for later migraine was increased by factors of 2.08, 21.87 and 3.93, respectively. The proportion of risk for migraine in primary school children explained by any episodic syndromes included in the International Classification of Headache Disorders was 2.18% and for any episodic syndromes not included in the International Classification of Headache Disorders it was 0.59%. Conclusion: Several pre-school episodic syndromes are risk factors for migraine in primary school age children. The fraction of migraine in primary school age children explained by prior episodic syndromes, however, is below 3%. A probability to develop primary school age migraine above 50% was only observed for abdominal migraine.